Tear deficiency transforms spatial distribution of corneal calcitonin gene-related peptide-positive nerves in rats - Kiyoi, Takeshi; Nakajima, Akihiro; He, Qiang; Liu, Li; Zheng, Shijie; Kobayashi, Shizuka; Uwada, Junsuke; Masuoka, Takayoshi (Frontiers in Cellular Neuroscience, 2025)
The nerve terminals distributed in the cornea are important for sensory perception and the maintenance of ocular surface homeostasis. In dry eye disease (DED), corneal nerves undergo functional and morphological changes that may be involved in abnormal ocular surface sensation and corneal pathology. However, changes in the spatial distribution of corneal nerves, including polymodal nociceptors, and their regulatory mechanisms remain unknown. In the present study, we analyzed time-dependent changes in corneal nerves, focusing on calcitonin gene-related peptide (CGRP)-positive nociceptive nerves in DED model rats, in which both the extraorbital and intraorbital lacrimal glands were surgically excised. After gland excision, the cornea showed acute inflammation, characterized by the presence of segmented-nucleus neutrophil infiltration, followed by chronic inflammation and angiogenesis. In parallel, denervation and subsequent reinnervation in the epithelium, as well as excessive innervation in the stroma, were observed, both involving CGRP-positive nerves. The DED rats showed hypoesthesia and subsequently hyperesthesia in response to mechanical stimulation of the corneal surface, which was synchronized with the denervation and reinnervation of corneal nerve plexuses in the epithelium. Persistent hyperalgesia to capsaicin in DED rats was not correlated with CGRP-positive nerve distribution in the early phase. After gland excision, the expression of neurotropic factor Sema7A increased within the epithelium and stroma, while that of the repulsive axon guidance factor Sema3A decreased in the epithelium. The expression patterns of these molecules correlate with reinnervation of the epithelium and excessive innervation of the stroma. These data suggest that changes in nerve distribution, including CGRP-positive nerves, might partially contribute to sensory perception and progression of corneal inflammatory pathology in DED. Sema3A and Sema7A may be involved in reinnervation as part of the regulatory mechanism in DED.